Should boys & girls be coached the same way? - Stewart, C. (coachesinfo.com)
The purpose of this study was to determine if gender differences existed in former athletes in their perceptions of 'favorite and least favorite' coach characteristics. Conclusions: In the examination of gender differences in sport behavior, Gill (1994) stated that investigation of these factors is more related to social and psychological characteristics than behaviors directly associated with a specific gender. In addition, she wrote that behaviors and characteristics are neither dichotomous nor biologically based, and the attempt to investigate them is elusive at best. As the society changes in which athletes exist, so do the gender roles of the athletes. The results of this study appear to support that belief. There were more similarities in how males and females remembered and characterized their favorite and least favorite coaches than differences. Both genders valued 'personality' above any characteristic as a positive attribute. While personality is a broad, general descriptor, it certainly provides future coaches with specific behaviors that players remember. Athletes of both genders characterized their favorite coaches as those who were assertive, cooperative, determined, respected (& respectable), willing to help, dedicated, a quality person, great personality, 'cool' under pressure, responsible, liked coaching, a role model, energetic, and wanted to be there. The memories of those athletes can provide future coaches with behavioral guidelines by which to develop their coaching styles. Other positive characteristics which were similar between genders were CARED AND COMMUNICATION. With both genders, these characteristics were remembered by coaching behaviors such as cared for me as a person, cared away from the game, talked to me about school, and asked me about things away from my sport. In contrast, males valued KNOWLEDGE (of the sport) and TEACHING SKILLS more than females. Females appeared to value EMOTION and POSITIVE characteristics of coaches more than males. These findings appear to support the thesis that females tend to be more internalized than males in some motivational aspects of sport. Females are apt to valued performance improvements based upon positive interactions and self-comparisons, while males base some motivational factors on externalized factors which would be impacted by a coach's KNOWLEDGE of the sport and the ability to TEACH. However, females remembered the lack of TEACHING SKILLS as a frequent negative characteristic just as male athletes had. In the comparison of negative memories, the genders were even more similar than with positive attributes of their former coaches. The only obvious differences were in NEGATIVE (more frequently noted by females) and WINNING (more with males). However, those differences were very small. These results seem to accentuate the similarities between the genders. Certainly being remembered as 'favorite' or 'least favorite' coach is not, in itself, an absolute measure of coaching effectiveness. However, since the subjects in this study were experienced athletes with extensive backgrounds in traditional sports, their input should be valued in the determination this area. It has been stated that, in general, most coaches do not understand female athletes as well as they should. That very likely remains true today. Sport clinicians and coach educators should spend more time exploring gender differences among athletes and emphasizing working with young female athletes more. Continued examination will assist coaches, and those who train them, in working with all athletes effectively. Finally, although qualitative data is difficult to analyze statistically, it does provide information that is valuable to provide coaches with knowledge on how players perceived and remembered their behaviors. This study represents but a small contribution to the determination of how best to coach athletes of either gender. Additional work like this is needed to establish other areas of similarities and differences.